Recall of delirium and related distress in elderly hospitalized patients: a prospective study - Maria Leonor Justino Moura (2022)
Background: Delirium is a very common neuropsychiatric disorder in elderly, with a significant physical and psychological burden. Much is still unknown about its psychological effects. This study aims to identify the proportion of patients who recall delirium and to analyse the distress caused by it. Also, this study aims to analyse the association between delirium recall and related distress and global psychological distress regarding hospitalization. Methods: This is a prospective study with elderly hospitalized patients in level-2 units of Intensive Care Medicine Department of a University Hospital. Exclusion criteria were a Glasgow Coma Scale total ≤ 11, brain injury, blindness, deafness or inability to communicate. Delirium was daily assessed with the Confusion Assessment Method. Delirium recall and related distress in patients were measured using Delirium Experience Questionnaire. Global psychological distress was assessed with Kessler Psychological Distress Scale. Results: From 105 patients, 38 (36.2%) developed delirium. Most patients did not remember the delirium episode (64.7%). Among those who remembered (35.3%), most described delirium as a distressing experience (75%). Delirium recall was associated with high global psychological distress (p=0.029). Distress related to delirium was also related with global psychological distress, although not statistically significant (p=0.222). Conclusions: Distress related to delirium is high, namely in patients who recall the episode. Global psychological distress during hospitalization is associated with delirium recall. This study highlights the need to assess the experience of delirium in these patients, as well as the importance of providing support and psychological interventions to minimize the associated distress.